Quando as armas do leviatã se voltam contra si: a greve da polícia militar do espírito santo de fevereiro de 2017 - Rocha, Guilherme Dall'Orto (2019)
From February 3rd to February 25th, 2017, the state of Espírito Santo recorded the biggest public security crisis in its history. Those days were marked by a vertiginous increase in the reports of property crimes and by an alarming number of crimes against the life of state citizens. The observed social chaos occurred due to a stoppage of military police-men's service, carried out as a result of blockades executed by their relatives in the exits of the state’s main cities’ Military Police battalions. The family movement, which was self proclaimed autonomous (without interference from the members of the corporation), pleaded for material and symbolic benefits to the military police, drawing up a list of claims addressed to the state government. In turn, as a response, the state government declared it was unable to negotiate because of the economic crisis experienced by the state in the moment, while also identified the movement as illegal, classifying it as a strategy used by the military police to make claims, that is, they understood that a veiled strike (or "white strike") had been taking place. The present work aims, primarily through documentary analyzes, focused on records made at the time, to outline the scenario that took place during such mobilization. Based on the studies of Political Process Theory and seeking further support in the analysis of the Theory of Rational Choice, the objective is to understand the event of political confrontation from its origins to its later consequences. In order to do so, we have analyzed the formation of a confrontation repertoire based on the previous history of mobilization of military police at a national level, the trajectory of local confrontation involving government and military police, the socioeconomic and political context at the outbreak of the strike, the mobilization forces employed by the military police, the actions taken by both parties during the development of the strike, the mechanisms of demobilization and social control employed by the government and, finally, the reverberations observed in the post-stoppage scenario